Rancang Bangun Aplikasi Website Laundry Sepatu Menggunakan Metode Prototype - Wardhani, Diky; Nevandri, Rifqi Nadhir (Jurnal Sistem Informasi Komputer ( SIKOM ), 2024)
The development of the Vroz Clean Shoes Benda Admin Portal Website is driven by the problems faced in developing its business, such as the lack of information to customers and the customer registration and transaction processes that are still carried out manually. Therefore, the author's goal is to require a Website-based Admin Portal for Vroz Clean Shoes Benda in Pamulang, South Tangerang, to overcome and provide solutions to these problems. This Admin Portal was created using the Prototype method using UML (Unified Modelling Language) design and Java and PHP programming languages with the Codeigniter framework. The result of this research is the Website-based Vroz Clean Shoes Benda Admin Portal, which functions to facilitate the owner of the Vroz Clean Shoes shoe laundry service in managing customer and transaction data reports, and helping business development. This information system does not experience errors when tested with the Usability Testing method, so this Admin Portal can be implemented at the Vroz Clean Shoes Benda shoe laundry service in Pamulang, South Tangerang. Based on the results of the study, the overall results of the Usability Testing stage were obtained where the percentage was very easy 20%, Easy 46%, Neutral 20%, Not Easy 10%, Very Not Easy 4%.